Foreign Direct Investment in Developing Countries The India and China Experience - Panda, Anwesha (Digital Repository of Theses - SSBM Geneva, 2023)
This paper will investigate the impact of Foreign Direct Investment (FDI) in developing countries. It will establish the dependencies between FDI, GDP, and economic growth. The paper will provide an analysis of the policy framework of both countries and will lay out suggestive measures to increase the FDI inflows. To what extent FDI impacts the host country’s economic growth will be studied in this paper. This paper will also analyze the impact of FDI on domestic industries.